2011
DOI: 10.1115/1.4004936
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Model for Axial Heat Conduction Effects During Single-Phase Flow in Microchannels

Abstract: A model is developed to analyze the effect of axial conduction on heat transfer during single-phase flow in microchannels. The axial heat conduction in the wall introduces heat flow toward the inlet section resulting in an increase in the local fluid temperature and a corresponding increase in the wall temperature. Neglecting this effect while reducing the experimental data results in a lower value of the experimental Nusselt number. The model derived in this work takes into account this effect and offers a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
0
28
2
Order By: Relevance
“…They found that the axial conduction effects in the wall are severe for gas flows through any tube material. Lin and Kandlikar [33] also found that axial conduction effects in the wall are negligible for water flowing through stainless steel microtubes, while for higher conductivity materials, it is not negligible even for water.…”
Section: Axial Back Conduction In Micro-sized Channelsmentioning
confidence: 95%
See 1 more Smart Citation
“…They found that the axial conduction effects in the wall are severe for gas flows through any tube material. Lin and Kandlikar [33] also found that axial conduction effects in the wall are negligible for water flowing through stainless steel microtubes, while for higher conductivity materials, it is not negligible even for water.…”
Section: Axial Back Conduction In Micro-sized Channelsmentioning
confidence: 95%
“…Lin and Kandlikar [33] have recently developed a theoretical model to analyze the effect of axial conduction on heat transfer during single-phase flow in microchannels. This model is based on the assumption that flow is thermally and hydrodynamically fully developed.…”
Section: Axial Back Conduction In Micro-sized Channelsmentioning
confidence: 99%
“…They also derived a set of equations, which were numerically solved to investigate these effects. Lin and Kandlikar (2012a) considered the axial conduction effects to cause an increased heat transfer to the fluid near the entrance region, leading to a higher heat transfer rate and a higher fluid temperature at any section in the heat exchanger. They derived the following equation to determine the Nusselt number in the presence of axial conduction effects.…”
Section: Axial Conduction Effectsmentioning
confidence: 99%
“…Lin and Kandlikar [15] developed a model to analyze the effect of LHC on heat transfer during single-phase flow in microchannels. The results showed for any tube material the effect of LHC in the wall was severe for gas flow and for water the effect of LHC in the wall was not negligible only for high conductivity channel material or thick channel wall.…”
Section: Introductionmentioning
confidence: 99%